1987
DOI: 10.1007/bf00464652
|View full text |Cite
|
Sign up to set email alerts
|

A correlation of the surgical anatomy of the dura to head and neck surgery

Abstract: Head and neck surgery may be complicated by penetration of the dura resulting in meningitis, cerebrospinal rhinorrhoea, cerebral abscess or other intracranial complications. The strength of the dura mater both protects the brain and spinal cord and makes dura an ideal material for grafting (when needed). This study examines the thickness and histological composition of dura mater at various sites encountered in head and neck surgery. Dura was removed from eight specified locations in 14 adult cadavers. Microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Willatt et al reported skull base dura to range from 0.72 to 0.88 mm and found that the tegmen middle cranial fossa dura was significantly thinner than frontal sinus, cribriform plate, anterior cranial fossa dura, and posterior cranial fossa dura. 19 Histological cadaveric studies in human spine also found variability in dural thickness not just between different segments and levels of the spine but also between ventral and dorsal dura. Kwon et al studied cervical spine dura and found a significant negative correlation with age but no difference among genders in a cohort of nine cadavers.…”
Section: Discussionmentioning
confidence: 99%
“…Willatt et al reported skull base dura to range from 0.72 to 0.88 mm and found that the tegmen middle cranial fossa dura was significantly thinner than frontal sinus, cribriform plate, anterior cranial fossa dura, and posterior cranial fossa dura. 19 Histological cadaveric studies in human spine also found variability in dural thickness not just between different segments and levels of the spine but also between ventral and dorsal dura. Kwon et al studied cervical spine dura and found a significant negative correlation with age but no difference among genders in a cohort of nine cadavers.…”
Section: Discussionmentioning
confidence: 99%
“…The outer layer is formed by the periosteum of the tabula interna, which is rich in blood and lymphatic vessels and nerves and the inner layer, the meningeal layer, lines the inside of the entire skull. Histological examination shows the similarity of these two layers [9] . The thickness of the dura varies depending on the location in the skull.…”
Section: Discussionmentioning
confidence: 92%
“…Folding the outer layer over the gap and suturing to the opposite dura border ( d ). dura mater is remarkably thicker in contrast to the dura covering the ethmoid sinus, the tegmen and the sigmoid sinus plate [9] . This has implications for the application of the proposed technique.…”
Section: Discussionmentioning
confidence: 92%
“…Metastasis cancer corrodes or invades the surrounding tissue. Since the dura thickness in the skull base was relatively thinner than other parts, [24] it was easier for cancer cells to breach the CSF leak-proof mechanism in the skull base. When the tumor is shrunken after surgery, the CSF may leak from those cracks made by cancer, and air may be drawn into the cranial space via the inverted soda bottle mechanism [16][17][18] or the ball valve mechanism.…”
Section: Discussionmentioning
confidence: 99%